Evolution of bower building in Lake Malawi cichlid fish: phylogeny, morphology, and behavior - York, Ryan A.; Patil, Chinar; Hulsey, C. Darrin; Anoruo, Onyemaechi; Streelman, J. Todd; Fernald, Russell D. (Frontiers in Ecology and Evolution, 2015)
Despite considerable research, we still know little about the proximate and ultimate causes behind behavioral evolution. This is partly because understanding the forces acting on behavioral phenotypes requires the study of species-rich clades with extensive variation in behavioral traits, of which we have few current examples. In this paper, we introduce the bower-building cichlids of the Lake Malawi adaptive radiation, a lineage with over 100 species, each possessing a distinct male extended phenotype used to signal reproductive fitness. Extended phenotypes are useful units of analysis for the study of behavior since they are static structures that can be precisely measured within populations. To this end we recognize two core types of bowers - mounds (“castles”) and depressions (“pits”). We employ an established framework for the study of adaptive radiations to ask how traits related to other stages of radiations, macrohabitat and feeding morphology, are associated with the evolution of pit and castle phenotypes. We demonstrate that pits and castles are evolutionarily labile traits and have been derived numerous times in multiple Malawi genera. Using public ecological and phenotypic data sets we find significant and correlated differences in macrohabitat (depth), sensory ability (opsin expression), and feeding style (jaw morphology and biomechanics) between pit-digging and castle-building species. Phylogeny-corrected comparisons also show significant differences in several measures of jaw morphology while indicating non-significant differences in depth. Finally, using laboratory observations we assay courtship behaviors in a pit-digging (Copadichromis virginalis) and a castle-building species (Mchenga conophoros). Together, these results show that traits at multiple biological levels act to regulate the evolution of a courtship behavior within natural populations.